KONSEP YURIDIS TENTANG PERKAWINAN YANG SAH DALAM GEREJA KATOLIK - I Made Markus Suma (Jurnal Euntes, 2022)
Having received the sacrament of Baptism, Christ’s faithful have been incorporated into the body of Christ, the Church. Since then, every baptized person has become a member of the Church. Based on this membership, every baptized in full communion with the Catholic Church acquires the right to marry (ius connubii). This right, however, is governed both by divine and ecclesiastical law and civil law in all civil effects brought about by marriage contracts. What are the canonico-juridico elements for a valid marriage in accordance with the norms of the Catholic Church? This work attempts to explore and expose the canonical norms concerning marriage in the Catholic Church and propose them as guidance for every Christ’s faithful to enter into a valid marriage.